QUINTIP RECORDATI INITIAL DATA CONCERNING THE PECULIARITIES OF HUMAN PAPILLOMAVIRUS INFECTION EPIDEMIOLOGY IN UKRAINE AND THE PROSPECTS FOR ITS PREVENTION - Rybin, A.I.; Osyk, V.V.; Vastyanov, R.S.; Liskovskyi, S.V.; Artyomenko, V.V. (World of Medicine and Biology, 2025)
The purpose of the study was to evaluate the human papillomavirus infection prevalence among women in different regions of Ukraine using the Quintip Recordati database. The Quintip Recordati database data, containing 195 records, was analyzed using frequency analysis methods. The distribution features of different HPV strains among the surveyed women living in other regions were determined. The frequency of seropositive results was analyzed also depending on the degree of urbanization. It was found that the number of positive tests was 38.5 % of the total sample size. When comparing the frequency of detection of highly oncogenic strains, it was found that they are more often registered in cities with a larger population. The authors showed that the prevalence of human papillomavirus infection in the surveyed women is twice higher comparing the average European level. Papillomavirus infection high prevalence in Ukraine is supposed to be the result of low vaccination coverage, lack of mass screening, lack of awareness and limited access to preventive programs. The frequency of detection of highly oncogenic HPV strains is higher in urbanized regions. The authors conclude that human papillomavirus infection diagnostic screening methods widespread implementation in Ukraine can significantly reduce the incidence of cervical cancer. They are sure that cervical cancer prevention will continue to rely on secondary prevention methods.